Acute kidney injury: Global health alert - Philip Kam Tao Li; Emmanuel A Burdmann; Ravindra L Mehta; Sara Martin (Society of Diabetic Nephropathy Prevention, 2013)
Acute kidney injury (AKI) is increasingly prevalent in developing and developed countries and is associated with severe morbidity and mortality. Most etiologies of AKI can be prevented by interventions at the individual, community, regional and in-hospital levels. Effective measures must include community-wide efforts to increase an awareness of the devastating effects of AKI and provide guidance on preventive strategies, as well as early recognition and management. Efforts should be focused on minimizing causes of AKI, increasing awareness of the importance of serial measurements of serum creatinine in high risk patients, and documenting urine volume in acutely ill people to achieve early diagnosis; there is as yet no definitive role for alternative biomarkers. Protocols need to be developed to systematically manage prerenal conditions and specific infections. More accurate data about the true incidence and clinical impact of AKI will help to raise the importance of the disease in the community, increase awareness of AKI by governments, the public, general and family physicians and other health care professionals to help prevent the disease. Prevention is the key to avoid the heavy burden of mortality and morbidity associated with AKI.